Effects of a Text-Processing Comprehension Intervention on Struggling Middle School Readers. Issue 4 (October 2016) - Barth, Amy E.; Vaughn, Sharon; Capin, Philip; Cho, Eunsoo; Stillman-Spisak, Stephanie; Martinez, Leticia; Kincaid, Heather
Abstract : Purpose: We examined the effects of a text-processing reading comprehension intervention emphasizing listening comprehension and expressive language practices with middle school students with reading difficulties. Method: A total of 134 struggling readers in grades 6–8 were randomly assigned to treatment ( n = 83) and control conditions ( n = 51) using a 2:1 ratio (two students randomized to treatment for every one student randomized to control). Students in the treatment condition received 40 min of daily instruction in small groups of four to six students for approximately 17 hr. Results: One-way analysis of covariance models on outcome measures with the respective pretest scores as a covariate revealed significant gains on proximal measures of vocabulary and key word and main idea formulation. No significant differences were found on standardized measures of listening and reading comprehension. Discussion: Results provide preliminary support for integrating listening comprehension and expressive language practices within a text-processing reading comprehension intervention framework for middle-grade struggling readers.